PENDAMPINGAN DAN PELATIHAN MANAJEMEN KEUANGAN DI UMKM BATIK SERASI MULYOREJO, SURABAYA - Ida Ayu Sri Brahmayanti; Gustaf Naufan Febrianto; Riyadi Nugroho (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The aim of this activity is to improve the economy of a productive society, Batik Serasi MSMEs in financial management are still not optimal and are still simple and even still mixed with personal finances. In running a business, finance is the spearhead of a business. Therefore, wise management of money, costs and budgets is very important for the continuity of a business. If money is not managed carefully, income and expenses will not be controlled properly, which can result in bankruptcy. Financial management is important to learn for those of us who want to use their money as effectively and efficiently as possible. Based on these dynamics, Batik Serasi UMKM was upgraded, especially regarding financial business management such as: Financial Recording, Understanding Cash Flow, Cost Control, Debt Management, Receivables Management, Wise Investment, Tax Planning, Financial Performance Evaluation, Training and Financial Planning Development. Long Term Future challenges will be increasingly complex and require you to be able to master everything related to current conditions, such as understanding a business's financial reports, budget planning, creating a company profile, product development, and market identification and customer communication. So that Batik Serasi MSMEs can develop and experience progress, especially from a financial perspective